A randomized clinical trial on the short‐term effects of 12‐week sacubitril/valsartan vs. enalapril on peak oxygen consumption in patients with heart failure with reduced ejection fraction: results from the ACTIVITY‐HF study. (12th October 2021) - Halle, Martin; Schöbel, Christoph; Winzer, Ephraim B.; Bernhardt, Peter; Mueller, Stephan; Sieder, Christian; Lecker, Laura S.M.
Abstract: Aims: ACTIVITY‐HF was a randomized, double‐blind, active‐controlled study, which assessed the short‐term effect of sacubitril/valsartan compared with the active comparator enalapril on improving maximal exercise capacity in patients with heart failure with reduced ejection fraction (HFrEF). Methods and results: A total of 201 ambulatory patients with HFrEF (left ventricular ejection fraction ≤ 40%, New York Heart Association class III) across 34 centres in Germany were randomized (1:1) to receive sacubitril/valsartan 97/103 mg bid ( n  = 103) or enalapril 10 mg bid ( n  = 98). The primary endpoint of the study was the change from baseline in peak oxygen consumption (VO2 ; adjusted to body weight) after 12 weeks, and the key secondary endpoint was change from baseline in peak VO2 after 6 weeks. The study population was predominantly male (81.1%) with a mean age of 66.9 years and a body mass index of 29.4 kg/m 2 . Change in peak VO2 from baseline to Week 12 was similar between sacubitril/valsartan and enalapril groups [least squares mean difference: 0.32 mL/min/kg; 95% confidence interval (CI) −0.21, 0.85; P  = 0.2327]. Similarly, no significant differences were observed between the two treatment groups in minute ventilation to carbon dioxide production slope, exercise capacity at first ventilatory threshold or Borg scale at either Week 6 or Week 12. Change in heart rate at first ventilatory threshold was lower in the sacubitril/valsartan group compared with the enalapril group at Week 12 (mean −3.75 bpm; 95% CI −7.03, −0.48; P  = 0.0248). The safety of sacubitril/valsartan was comparable to enalapril. Conclusion: In patients with HFrEF, short‐term treatment with sacubitril/valsartan for 12 weeks did not result in significant benefits on peak VO2 when compared with enalapril. Abstract : Sacubitril/valsartan over 12 weeks compared with enalapril did not significantly improve peak oxygen consumption (VO2 ) in patients with heart failure with reduced ejection fraction (HFrEF). CI, confidence interval; LSM, least squares mean; LVEF, left ventricular ejection fraction; NYHA, New York Heart Association; SE, standard error.